Materials for hydrogen storage at room temperature – An overview. (2023) - Meduri, Sitaram; Nandanavanam, Jalaiah
Abstract: Given the environmental concerns, scientists are exploring sustainable and eco-friendly energy sources over the years. Hydrogen (H2 ), a green fuel, stands as a promising candidate for the future. It is been stored as either gas-, liquid- or solid-state. Storing hydrogen in solid form, through either physisorption or chemisorption, promotes it for effective use in the transportation sector. Physisorption is completely reversible and exhibits rapid kinetics, but suffers from low operating temperatures. The weak van der Waals forces here cause a decrease in storage capacity with a rise in temperature. Chemisorption offers higher hydrogen storage capacities but constrained by slow kinetics and high dehydrogenation temperatures. At room temperature, the H2 storage capacity ranges from 0.14 to 8.8 wt% for materials under undoped to doped conditions. Various techniques like the spillover mechanism, chemical activation (for adsorption), and ball milling, using catalysts, nanoconfinement (for absorption) help improve the hydrogen uptake at room temperature. This paper provides an overview on materials suitable for storing hydrogen at room temperature. It also discusses the critical issues and challenges in developing able materials for hydrogen storage at room temperature.